ORANG TUA MULTI ETNIK DI KOTA TANJUNG BALAI: GAYA PENGASUHAN DAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Mhd Habibu Rahman (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2020)
This paper presents the style of care adopted by multi-ethnic parents whose ethnicity includes Asahan and Toba Bataks. The parenting style of each parent is certainly different. This difference is triggered by several factors, one of which is culture. The culture carried by parents will affect the style of care and will have an impact on aspects of the child's development, including the child's emotional social. This study aims to determine the type of care done by multi-ethnic parents, and determine the factors that influence the social emotional development of children with multi-ethnic care. The results of the study illustrate that the culture of 7 parents in the city of Tanjung Balai causes a fusion of parenting or what is called parenting acculturation. Parenting styles adopted by parents affect the child's emotional social development. The parenting style applied by multi-ethnic parents in Tanjung Balai is permissive, and authoritative, which is relatively consistent over time. Permissive parenting style applied by multi-ethnic parents tends to give full freedom to children in making decisions and never gives an explanation or direction to the child, there is no stimulus, control and control to the child. While authoritative parenting styles tend to have strong principles towards culture, be rational, always base their actions on thought, pay attention to children's development, and direct the child to be able to behave rationally. The impact of multi-ethnic care is that children are able to recognize their own feelings, but have not been able to adapt to environmental situations, children have a great determination in completing play activities, this is supported from the care of Toba Batak culture which tends to be hard, and holds sufficient principles strong. Several factors influence the emotional social development of children from the care of multi-ethnic parents in the city of Tanjung Balai, namely the attitude and temperament of parents, the level of social activity, and the number of children.Keywords: Parenting style, Multi Ethnic, Emotional Social early childhood